Development The Scientific Contact of Teching Methods by Using Modern Education at Baghdad University (Al-Mansour Journal, 2023)
The research aims to publicize the importance of entrances and the use of modern techniques and advances in the field of modern education. The research and technology trends of modern education, which contributed to the emergence of new and sophisticated systems of teaching and learning that have had the greatest impact on changes and developments in accordance with the positive way in which students learn the techniques, methods and delivery of scientific information to them and their impact on the content and form of curriculum commensurate with these trends. The importance of improving the academic performance of the functions of Universities of Iraq faculty members through participation in sustainable development programs that require a scientific and strategic planning provide opportunities to develop their skills and raising the quality of teaching performance, and promotion of research skills and the provision of services appropriate scientific quality, and ensure the appropriateness of academic programs to the needs of the times and the needs of the community .